2004
DOI: 10.1038/sj.bjc.6601602
|View full text |Cite|
|
Sign up to set email alerts
|

Inactivation of class II transactivator by DNA methylation and histone deacetylation associated with absence of HLA-DR induction by interferon-γ in haematopoietic tumour cells

Abstract: By presenting immunogenic peptides at the cell surface, major histocompatibility complex (MHC) class II molecules play a key role in the control of adaptive immune responses. Whether expressed constitutively or induced by interferon-g, expression of MHC class II molecules is regulated via coactivator class II transactivator (CIITA); moreover, suppression of their expression is one mechanism by which cancer cells escape host immunity. In this study, we surveyed the relationship between the expression of one MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 38 publications
2
64
0
Order By: Relevance
“…From this standpoint, we recommend that the authors will clarify the relation of CIITA methylation status to constitutive expression of HLA-DR in a larger cohort of haematopoietic tumour. On the basis of their finding (Morimoto et al, 2004) and our present finding, in our opinion, methylation status of CIITA could be a therapeutic target combined with interferon-gamma for preventing the progression of haematopoietic tumour and HLA-DR may be superior to CIITA as a marker for progression of haematopoietic tumour.Additionally, tumour HLA-DR might have a function other than the antigen-presenting function. Recently, Altomonte et al (2003) showed a possible involvement of HLA-DR in a signalling pathway linked to cell adhesion in melanoma cells.…”
supporting
confidence: 69%
See 4 more Smart Citations
“…From this standpoint, we recommend that the authors will clarify the relation of CIITA methylation status to constitutive expression of HLA-DR in a larger cohort of haematopoietic tumour. On the basis of their finding (Morimoto et al, 2004) and our present finding, in our opinion, methylation status of CIITA could be a therapeutic target combined with interferon-gamma for preventing the progression of haematopoietic tumour and HLA-DR may be superior to CIITA as a marker for progression of haematopoietic tumour.Additionally, tumour HLA-DR might have a function other than the antigen-presenting function. Recently, Altomonte et al (2003) showed a possible involvement of HLA-DR in a signalling pathway linked to cell adhesion in melanoma cells.…”
supporting
confidence: 69%
“…In this regard, elegant work by Morimoto et al (2004) could provide a therapeutic strategy against various malignancies. The authors stated that, by suppressing the expression of MHC class II molecules, epigenetic inactivation of CIITA provided a survival advantage to a subset of haematopoietic tumours (Morimoto et al, 2004); however, they did not investigate the relation between levels of CIITA and HLA-DR and tumour progression.…”
Section: Sirmentioning
confidence: 99%
See 3 more Smart Citations